2013
DOI: 10.1016/j.jams.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Properties and Mechanism of Action of Orthosiphon stamineus Benth Bioactive Sub-fraction in Streptozotocin-induced Diabetic Rats

Abstract: Orthosiphon stamineus is a popular folk medicine widely used to treat many diseases including diabetes. Previous studies have shown that the sub-fraction of chloroform extract was able to inhibit the rise of blood glucose levels in a glucose tolerance test. This study was carried out to evaluate the chronic effect and possible mechanism of action of the bioactive chloroform sub-fraction of O. stamineus using streptozotocin-induced diabetic rats and in vitro methods. Administration of the chloroform extract sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…The UPLC method developed for the first time by Pang et al [10] is capable of a fast and accurate qualitative and quantitative analysis of polyphenols from O. stamineus extract. The analysis time is less than 7 minutes, as shown in Figure 1, which is about three times faster than those of the other reported methods [3,17]. The UPLC chromatogram shown in Figure 1 suggests that the presence of maltodextrin or whey protein does not affect polyphenol separation in the HSS T3 column.…”
Section: Uplc Quantification Of Polyphenolsmentioning
confidence: 80%
See 1 more Smart Citation
“…The UPLC method developed for the first time by Pang et al [10] is capable of a fast and accurate qualitative and quantitative analysis of polyphenols from O. stamineus extract. The analysis time is less than 7 minutes, as shown in Figure 1, which is about three times faster than those of the other reported methods [3,17]. The UPLC chromatogram shown in Figure 1 suggests that the presence of maltodextrin or whey protein does not affect polyphenol separation in the HSS T3 column.…”
Section: Uplc Quantification Of Polyphenolsmentioning
confidence: 80%
“…O. stamineus is traditionally used in Malaysia for treatment of bladder inflammation, eruptive fever, oedema, hepatitis, jaundice, hypertension, diabetes mellitus, gout, rheumatism, diuretic problems and influenza [1]. Previous studies revealed that extract of O. stamineus contained many medically useful bioactive compounds such as terpenoids, polyphenols and sterols that provide diuretic [2], antidiabetic [3], antiangiogenic and antiproliferative properties [4]. O. stamineus contains many useful active components such as rosmarinic acid, sinensetin and eupatorin, which can be recovered through the extraction process.…”
Section: Introductionmentioning
confidence: 99%
“…The healing power of Java Tea plant is because of its great chemical contents (Engku Hasmah, Ahmad Tarmizi, Noor Ismawaty and Abdul Ghani, 2012) and sufficient literature on this remarkable plant claims that it can be used to cure chronic diseases such as Diabetics, High Blood Pressure, Blood Circulation Disorder, Gout and Rheumatism and Kidney Stones (Cicero et al, 2012;Dole ckov a et al, 2012;Mohamed et al, 2013).…”
Section: Herbs Potential In Catalysing Economic Growthmentioning
confidence: 99%
“…Tea made from the leaves and roots of this plant is believed to ameliorate various pathologic conditions, such as rheumatic arthritis, diabetes, hypertension, tonsillitis, epilepsy, menstrual disorders, gonorrhea, syphilis, renal calculus, and urinary lithiasis [12,13]. Recently, other beneficial effects were reported, including antidiabetic, anti-inflammatory, antiproliferative, and antiangiogenic activities [14,15,16,17,18]. Moreover, several previous reports have provided evidence for the metabolic effects of OS.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Son et al [19] reported that crude OS extract elevates plasma levels of insulin in rats, while Choi et al [20] demonstrated the leptin stimulating effect of OS both in vitro and in vivo . Mohamed et al [18] also showed that OS exerts antidiabetic effects in streptozotocin (STZ)-diabetic rats. However, we still do not know whether OS stimulates insulin production or protects β-cell from glucotoxicity.…”
Section: Introductionmentioning
confidence: 99%